Effectiveness of the first district-wide programme for the prevention of mother-to-child transmission of HIV in South Africa - David Coetzee; Katherine Hilderbrand; Andrew Boulle; Beverley Draper; Fareed Abdullah; Eric Goemaere (The World Health Organization, 2005)
OBJECTIVE: The aim of this study was to estimate the field efficacy of the first routine programme for the prevention of mother-to-child transmission (PMTCT) of human immunodeficiency virus (HIV) initiated in South Africa, in the subdistrict of Khayelitsha. METHODS: A consecutive sample of 658 mother-infant pairs, identified from the PMTCT register from 1 March to 30 November 2003, were identified for enrolment in this study. Details of the regimen received were established and HIV status of the infants at between 6 and 10 weeks of age was determined by qualitative DNA polymerase chain reaction. Zidovudine (AZT) was provided antenatally from week 34 of gestation and during labour. Infant formula milk was offered to mothers who chose not to breastfeed. The protocol was amended in July 2003 such that women who had received < 2 weeks of treatment with AZT were given a single dose of nevirapine (NVP) at the onset of labour, and the infant received a weight-adjusted dose of NVP within 72 h of delivery. RESULTS: Of the 535 mother-infant pairs (81%) eventually included in the study, 410 (77%) received an effective PMTCT intervention according to the protocol. The rate of transmission of HIV from mother to child was 8.8% (95% confidence interval (CI), 6.2-10.9). A maternal age of > 25 years was the only significant independent risk factor for transmission (odds ratio, 2.12; 95% CI, 1.14-4.07). CONCLUSION: The results of this study demonstrate the feasibility and effectiveness of a large-scale PMTCT programme in an urban public-sector setting.